An analysis of funding patterns in development assistance for mental health: who, when, what, and where. (8th January 2021) - Gribble, Rebecca S. F.; Liese, Bernhard H.; Wickremsinhe, Marisha N.
Abstract: Background: Mental health has recently gained increasing attention on global health and development agendas, including calls for an increase in international funding. Few studies have previously characterized official development assistance for mental health (DAMH) in a nuanced and differentiated manner in order to support future funding efforts. Methods: Data from the Organisation for Economic Cooperation and Development Creditor Reporting System were obtained through keyword searches. Projects were manually reviewed and categorized into projects dedicated entirely to mental health and projects that mention mental health (as one of many aims). Analysis of donor, recipient, and sector characteristics within and between categories was undertaken cumulatively and yearly. Findings: Between the two categories of official DAMH defined, characteristics differed in terms of largest donors, largest recipient countries and territories, and sector classification. However, across both categories there were clear and consistent findings: the top donors accounted for over 80% of all funding identified; the top recipients were predominantly conflict-affected countries and territories, or were receiving nations for conflict-affect refugees; and sector classification demonstrated shifting international development priorities and political drivers. Conclusion: Across DAMH, significant amounts of funding are directed toward conflict settings and relevant emergency response by a small majority of donors. Our analysis demonstrated that, within minimal international assistance for mental health overall, patterns of donor, recipient, and sector characteristics favor emergency conflict-affected settings. Calls for increased funding should be grounded in understanding of funding drivers and directed toward both emergency and general health settings.